MODELING OF SPECIALIZED SCHOOLS: THEORETICAL AND PRACTICAL ASPECTS - Ivaniuk, Hanna I. (Educological discourse, 2015)
In the article the basic methodological approaches to modeling school profile is highlightsd. Substantiates the ones that allow the fullest disclosing the potential of rural schools, namely close ties with socio-cultural environment; internal differentiation, which is determined by personal meaning students for specialized professional oriented school. The content of the article developed based on the results of the theoretical analysis of the results of problems in modeling educational systems and study the status of specialized schools in rural areas. It is posted algorithm of simulation profile (upper secondary) schools, considering specific factors of educational environments in rural areas. Summary and recommendations presented in the content may be occasional to develop concepts profile education and specialized modeling schools in rural areas.